Mental disorders among pregnant women during the COVID-19 pandemic: A cross-sectional study - Keskin, Deha Denizhan; Keskin, Seda; Bostan, Sedat (São Paulo Medical Journal, 2022)
BACKGROUND: Pregnancy is the most important event in women’s lives and can lead to psychological lability. Several risk factors (such as disasters, events and pandemics) have been correlated with greater prevalence of mental disorders during pregnancy. OBJECTIVES: To research how pregnant women have been affected by the coronavirus disease-19 (COVID-19) pandemic process, in order to contribute to the limited literature. DESIGN AND SETTING: Cross-sectional survey study conducted at the Training and Research Hospital of the Faculty of Medicine, University of Ordu, Ordu, Turkey, from February 1 to March 1, 2021. METHODS: In total, 356 pregnant women were enrolled and completed the survey. Intention of going to hospital and the Beck anxiety, Beck depression, Beck hopelessness and Epworth sleepiness scales were applied to detect mental disorders. RESULTS: Among the participants, the anxiety, depression, hopelessness and sleepiness scores were 29.2%, 36.2%, 58.1% and 11.8%, respectively. The pregnant women stated that they avoided going to hospital in unnecessary situations by obeying the ‘stay at home’ calls, but also stated that they were afraid of the potential harmful effects of inadequate physician control. However, most of them stated that they would go to the hospital in emergencies. CONCLUSIONS: This paper illustrated the effect of the COVID-19 pandemic on the mental health of pregnant women and emphasized their high rates of anxiety, depression, hopelessness and sleepiness. Since presence of mental disorders is indirectly related to poor pregnancy outcomes, preventive strategies should be developed, especially during this pandemic process.